Effect of Iodine treatments on Ocimum basilicum L.: Biofortification, phenolics production and essential oil composition. - Claudia Kiferle; Roberta Ascrizzi; Marco Martinelli; Silvia Gonzali; Lorenzo Mariotti; Laura Pistelli; Guido Flamini; Pierdomenico Perata (PLoS ONE)
Iodine biofortification has been gaining interest in recent years as a sustainable and innovative approach to eradicate iodine deficiency disorders. Studying the impact of iodine biofortification on plant phenotype, biochemical and physiological parameters is crucial to leverage the expertise and best practices for the agro-food industry and human health. The aim of this study was to evaluate iodine biofortification on the main quantitative and qualitative traits of basil (Ocimum basilicum L.) plants cultivated both in open field and in growth chamber. The impact of KI and KIO3 treatments was evaluated on biomass production, as well as on the synthesis of phenolic compounds, especially rosmarinic acid and other caffeic acid derivatives, and on the essential oil (EO) composition. These compounds are typically accumulated in basil leaves and strongly contribute to the plant nutraceutical value and aroma. In open field, the use of increasing concentrations of both iodine salts gradually enhanced iodine accumulation in leaves, also determining an increase of the antioxidant power, total phenolics, rosmarinic acid and cinnamic acid accumulation. The composition of EO was only slightly affected by the treatments, as all the samples were characterized by a linalool chemotype and a minor alteration in their relative content was observed. A growth chamber experiment was performed to test EO variation in controlled conditions, broadening the range of iodine concentrations. In this case, plant chemotype was significantly affected by the treatments and large EO variability was observed, suggesting that iodine form and concentration can potentially influence the EO composition but that in open field this effect is overcome by environmental factors.